Anatomic shoulder replacement for primary osteoarthritis in patients over 80 years - Iriberri, Iker; Raiss, Patric (European archives of psychiatry and clinical neuroscience, 2015)
Anatomic total shoulder arthroplasty (TSA) gives good outcome in the treatment of primary osteoarthritis, but it is not known whether this also applies to patients over 80 years old. Patients and methods — We retrospectively assessed outcome in patients over the age of 80 after anatomic TSA, performed for primary osteoarthritis with a preoperative intact rotator cuff (group O, n = 32). We compared it with outcome in a group of patients under the age of 70 (group Y, n = 32). Subjective outcome, Constant score, and radiological findings were analyzed. Results — At a mean follow-up time of 7 years, there were no statistically significant differences between the groups. In group O, 24 patients were very satisfied and in group Y, 23 patients were very satisfied; the subjective shoulder value was 81% in both groups. Mean Constant score was 65 in group O and 67 in group Y. Moderate or severe radiological upper migration of the humeral head was detected in 1 patient in group O and in 3 patients in group Y. One patient in group Y was revised for glenoid loosening. Interpretation — Good to excellent results can be expected after anatomic TSA in patients over the age of 80. Our findings suggest that they have similar results to those in patients around 70 years of age.